EFEKTIVITAS PEMBERIAN EKSTRAK GEL BELIMBING MANIS (Averrhoa carambola Linn) TERHADAP KESEMBUHAN ULKUS TRAUMATIKUS Studi In Vivo terhadap mukosa Tikus (Strain Wistar) - Arief Pramono; Bawa Adiwinarno; Lisa Oktaviana Mayasari (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
Background of the Study: Ulcers is often founded on society which causes pain, difficulty in speaking, eating, or swallowing. Indonesia is one of tropical countries which has a lot of natural resources. Since a long time ago, Indonesian citizen is close to various fruits, particularly starfruit. (Averrhoa carambola L). Objectives: To know the effectivity of the concentration from starfruit gel extraction (Averrhoa carambola L)towards traumatic ulcers. Methods: About 24 Mistar mice are divided into 4 groups. Hyaluronic acid 0.2% (K1), starfruit gel extraction 25% (P1), starfruit gel extraction 50% (P2), and starfruit gel extraction 75% (P3). The adaptation of the mice happens for a week. On the firstday, ulcers on labial mucosa is made on the mouse using the tip of amalgam stopper which is heated. It spreads on once a day, and the measuring is done on the first day, third day, fifth day, and seventh day using calipers. The data result is analyzed by using one-way anova and post hoc LSD test. Results: Based on the test result using one-way anova, it shows the significant result of each group (0.00) so that there is contrast on giving extract gel of 25%, 50%, and 75%. Based on post hoc LSD test, it points out that hyaluronic acid 0.2% (K1) towards starfruit gel extraction on concentration of 25% do not show substansial contrast about 0.473, whereas extract gel of 50% and 75% shows significant contrast of 0.000 (p<0.05). The group of starfruit gel extraction which has concentration of 25% (P1) towardsextract gel of 50% and 75% shows that there  is significant  contrast as much  as 0.000.  The group  of extract  gel  starfruit  which  have concentration 50% (P2) towards extract gel of 75% (P3) do not show significant contrast as much as 0.215. Conclusion: Hyaluronic acid 0,2% and starfruit gel extraction 25%, 50%, 75% have influence towards the recovery of traumatic ulcers and starfruit gelextraction 50% and 75% is the most effective concentration on hastening the healing process traumaticulcers. Keywords: Averrhoa carambola Linn., traumatic ulcer, wound healing, hyaluronic acid